Factori inhibitori ai inovației în serviciile sociale - Arpinte, Daniel (Calitatea Vieții, 2010)
The article analyses the main issues which might hinder the innovative approach in social work services. The first part describes the context of the social work development in Romania, based on a comparative approach. In the second part are presented the main factors for lack of innovation: the lack of strategic vision, the financial arrangements, the institutional framework and the influence of international institutions.